More Than 20 Years Follow-up After En Bloc Cervical Laminoplasty. Issue 20 (15th October 2016) - Kawaguchi, Yoshiharu; Nakano, Masato; Yasuda, Taketoshi; Seki, Shoji; Hori, Takeshi; Suzuki, Kayo; Makino, Hiroto; Kanamori, Masahiko; Kimura, Tomoatsu
Abstract : Study Design: Retrospective study. Objective: The aim of the study was to evaluate clinical outcomes and to clarify the potential risks of cervical laminoplasty by a long-term follow-up of more than 20 years. Summary of Background Data: There is no follow-up report exceeding 20 years after cervical laminoplasty. Methods: Two hundred sixteen patients underwent en bloc cervical laminoplasty for the treatment of cervical compressive myelopathy due to cervical spondylosis or ossification of the posterior longitudinal ligament between 1981 and 1994. Of these, 148 patients with a follow-up of more than 20 years were retrospectively studied (68 survived patients and 80 dead patients). The neurological evaluation was graded using Japanese Orthopaedic Association (JOA) score and the recovery rate. Neurological recovery was defined by the increase in JOA score. Radiological examinations were carried out using pre- and postoperative radiographs. As for the dead patients, the cause and age of death were reviewed. Results: The JOA score and recovery rate increased to 14.2 ± 2.7% and 64.9 ± 28.6%, respectively, at 5 years. The JOA score and recovery rate were maintained at 13.9 ± 3.2% and 61.6 ± 34.6% at 10 years. The JOA score decreased to 11.4 ± 5.1 at the last follow-up. In 32 out of 65 patients (49.2%), the JOA scores worsened mainly due to other spinal lesions. Cervical alignment became kyphotic when comparing preoperatively and at the last follow-up (ossification of the posterior longitudinal ligament: 15.7 ± 12.2° and 6.9 ± 17.8°, cervical spondylosis: 11.0 ± 8.9° and 3.3 ± 9.4°). Range of motion (ROM) decreased and one of the causes of ROM reduction was interlaminar fusion. The mean age at death was 78.2 years. The most frequent cause of death was malignant tumor. Conclusion: Spine surgeons must be aware that patients have a long postoperative lifetime when cervical laminoplasty is performed. A long postoperative follow-up should be carried out after laminoplasty. Level of Evidence: 4